Eosinophilic Pleuritis due to Sparganum: A Case Report - Oh, Youngmin (The Korean Society for Parasitology and Tropical Medicine, 2014)
Sparganosis is a rare parasitic disease caused by migrating plerocercoid tapeworm larva of the genus Spirometra. Infection in humans is mainly caused by the ingestion of raw or inadequately cooked flesh of infected frogs, snakes, and chickens. Here, we report a rare case of a 45-year-old man who was admitted to our hospital with left lower chest pain. The chest radiograph and computed tomography (CT) scan revealed localized pleural effusion in the left lower lobe; further, peripheral blood eosinophilia and eosinophilic pleural effusion were present. Percutaneous catheter drainage was performed, which revealed long worm-shaped material that was identified as a sparganum by DNA sequencing. The patient showed clinical improvement after drainage of the sparganum. This study demonstrates the importance of considering parasitic diseases in the differential diagnosis of eosinophilic pleural effusion.